Faktor-faktor yang berpengaruh terhadap kecukupan energi rumah tangga di perdesaan - slamet iskandar (Health Sciences and Pharmacy Journal, 2019)
Based on the Food Balance Sheet for Daerah Istimewa Yogyakarta (DIY) in the period of 2006-2015, the condition of food availability was sufficient, but there were still some villages that suffered food insecurity and malnutrition. This study aims to determine the factors that influence adequacy the energy of household food consumption in rural DIY. The population of this study was 1,160 households from secondary data from the 2015 Susenas in DIY. The research sample were 571 households, taken by purposive sampling with criteria in one household there was a husband and wife. Data was taken by questionnaire. The design of this study was cross sectional. Data was analyzed by applying Ordinary Least Square (OLS). The average adequacy of household energy attained about 90,85%. There was a significantly positive influence of maternal age, income, raskin recipient households, employment on household energy sufficiency and otherwise the household members and poor category household on household energy sufficiency.